Implications of modernity on Chinese funeral rituals and the continued success of the funeral industry in Singapore. - Moo, Emily Li Ling (Nanyang Technological University, 2021)
The inevitability of life is death. While emotions surrounding the loss of a loved one is complex, people ultimately have to manage the practical reality of a passing. Funeral rituals seek to mitigate disorder and disruption for the living, as enactment of ritualized actions provide a sense of acknowledgement of loss in the sending off of the deceased. As ways to die proliferate, so do ways to memorialize. Paraphrasing Derrida, “while all people die, they do not die alike”. Similarly, they do not grieve alike. How societies prioritize and assign precedence in loss are informed by social and material conditions of a specific time and place. The religious Chinese believe that death is not the end. It is merely a point of transition. The reciprocal relationship between the dead and the living reinforces the importance of rituals, ensuring the process of continual exchange between family and ancestors. Being a Chinese in post-independence Singapore (1965-2020) is not as straightforward as one thinks. This paper illuminates how the syncretic religion and subsequent identity of the religious Chinese community came to be through the study of imperial Chinese funeral rituals as well as the contestation between a modernising state and the survival of the funeral industry in post-independent Singapore – which relates to our broader understandings of how rituals reinstate the religious Singaporean Chinese identity as well.